2013
DOI: 10.1016/j.measurement.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

COMSOL Multiphysics validation as simulation software for heat transfer calculation in buildings: Building simulation software validation

Abstract: Abstract* gerlich@fai.utb.cz, tel.: +420 57 603 3012The main purpose of this article is a presentation of software validation for a calculation of heat transfer in Greek symbolsDensity (kg/m 3 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Several of those already tested by IEA are EnergyPlus, FLUENT, Matlab, TRNSys, GHT and ANSYS Fluent. As you can see in [21] COMSOL Multiphysics was validated at authors department, where simulated data showed agreement with the rest energy simulation software as well as with analytical solution.…”
Section: Numerical Simulationsmentioning
confidence: 75%
“…Several of those already tested by IEA are EnergyPlus, FLUENT, Matlab, TRNSys, GHT and ANSYS Fluent. As you can see in [21] COMSOL Multiphysics was validated at authors department, where simulated data showed agreement with the rest energy simulation software as well as with analytical solution.…”
Section: Numerical Simulationsmentioning
confidence: 75%
“…In the software model, temperature contours show all the areas with the same unique temperature compared to their surrounding area [22]. Since our heating process in the experimental test was not uniform, the heated areas are different in the software results from the actual experimental results especially on the deeper defected area.…”
Section: Modeling the Ir Testmentioning
confidence: 99%
“…The validation of COMSOL's heat transfer modules is documented in different studies. [15][16][17] A typical COMSOL simulation comprises of choosing the physics and solver type, defining geometry and materials, applying appropriate boundary conditions and meshes.…”
Section: Computational Proceduresmentioning
confidence: 99%